Plantas de cobertura do solo e época de poda na videira em região tropical - Campos, Luiz Fernandes Cardoso (2014)
The cultivation of the vine in the State of Goiás is already a reality and has good growth prospects, but there is little information about soil management, particularly regarding the use of cover crops in the vineyards soil. The use of management techniques aimed at improving the production system, accordingly the proper management of soil and vine canopy can influence yield and quality of grape. Therefore the objective of this study was to evaluate the development, the rate of decomposition and accumulation of nutrients in the shoots of ground cover grown intercropped with vine, besides the chemical characteristics of the soil and the nutritional status, growth and production of fruit species as well as the qualitative characteristics of the fruits. The experiment consisted of six treatments established in a randomized block design, in 3 x 2 factorial scheme, with five replicates. The first factor with three levels, was composed of the following plant species cover crops: bean-to-pig (Canavalia ensiformis L. DC), lab-lab (Dolichos lab lab L.) and weeds. The second factor, with two levels of pruning were carried out based on the seeding of cover crops. Ie, the first season pruning was done 25 days after sowing (DAS) of the cover crop and the second season of pruning performed at 55 DAS. Each plot of 9 m2 (2 x 4.5 m) contained two vine plants. Pruning times do not influence the rate of soil cover and biomass production by cover crops. The weeds provide the highest rates of soil cover. The bean-to-pig has higher production of plant biomass (dry and green). Plants have evaluated coverage rate similar decomposition, pruning times do not affect the decomposition of the cover crop. The fabaceae stand on the accumulation and release of nutrients, but it does not differ from wild plants, the change in the soil chemistry. Cover crops did not influence the nutritional status of the vine. The morphologic parameters of vine plants Isabel are not influenced by ground cover plants. Cover crops influence soil not the vine as productivity and related variables. Of pruning influencing productivity and related variables in vineyards. Qualitative characteristics of the grape plants are not affected by ground cover, pruning times can influence the composition of the wort.